Sleep-related rhythmic movement disorder in children: a mini-review - Lam, Nhi; Veeravigrom, Montida (Frontiers in Neurology, 2023)
Sleep-related rhythmic movement disorder (SRRMD) occurs in both infants and children. This disorder rarely occurs or persists in adolescence or adulthood. Rhythmic movement during sleep in children is often asymptomatic and considered a benign condition. It is classified as SRRMD when movement significantly disrupts sleep, results in daytime functional impairment, or causes self-inflicted body injury. Several studies have demonstrated that SRRMD occurs in all sleep stages. Few studies have investigated rhythmic movement disorder (RMD) in children. SRRMD is a clinical diagnosis supported by home video recordings. When the clinical history is insufficient to provide a definitive diagnosis of SRRMD, and other sleep-related conditions or seizure disorders are suspected, video-polysomnography is indicated. There are currently no clinical guidelines for treating SRRMD.